HUBUNGAN KEPADATAN HUNIAN DAN VENTILASI RUMAH DENGAN KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS ULUGALUNG, KECAMATAN EREMERASA KABUPATEN BANTAENG - Andi Suswani; Aszrul AB (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2018)
ARI is still one of the important public health issues because it is an acute disease and can even cause death. Seeing the phenomena that exist and based on the results of research obtained in the Work Area of ​​Eremerasa Community Health Center, Ulugalung Village is one of the villages that have dense residential problems that suffer from ARI as many as 40 people caused by the level of occupancy density. This study aims to identify the relationship between Residential Density and Ventilation of Houses with ISPA Events in Toddlers in the Working Area of ​​Ulugalung Health Center, Eremerasa District, Bantaeng Regency. This research is a quantitative analytic observational design with Case Control approach. The sample in the study was chosen by Purposive sampling technique as many as 68 respondents. The results showed that the relationship between occupancy density and the incidence of ARI (p = 0,000) and there was no correlation between home ventilation and the incidence of ARI (p = 0.116). In other words there is a significant relationship between the relationship between occupancy density and the incidence of ARI in the Work Area of ​​Ulugalung Health Center, Eremerasa District, Bantaeng Regency.